PENGARUH NILAI PELANGGAN, KEPUASAN, DAN KEPERCAYAAN TERHADAP LOYALITAS PENUMPANG MASKAPAI GARUDA INDONESIA DI BANDAR UDARA JALALUDDIN GORONTALO - Karundeng, Deby Rita; Suyanto, Mohamad Afan; Usu, Idrus; Rahman, Stephany (Bussman Journal : Indonesian Journal of Business and Management, 2024)
This study aims to analyze the influence of customer value, satisfaction, and trust on the loyalty of passengers of Garuda Indonesia Airlines at Jalaluddin Gorontalo Airport. Using the accidental sampling method, data were obtained from 97 respondents. The analysis method employed was multiple linear regression. The results indicate that, partially, customer value, satisfaction, and trust have a positive and significant impact on passenger loyalty. Furthermore, these three factors collectively contribute significantly to passenger loyalty. These findings offer valuable insights for airline management to enhance customer experience and maintain their loyalty